Utilizing Recycled Materials as Innovative Educational Media to Enhance Early Childhood Learning - Royani, Ida; Suriyani, Suriyani; Tjahyaningsih, Ririn (International Journal Education and Computer Studies (IJECS), 2025)
Abstract This research investigates the use of recycled materials as educational media designed to enrich early childhood learning experiences. The study aims to understand how these materials affect children’s participation, foster creativity, support cognitive growth, and build environmental awareness. Using a qualitative descriptive approach, data were gathered through observation, interviews, and documentation at a local early childhood education center. Results indicate that learning activities involving recycled items promote higher levels of student engagement and help develop fine motor skills, while also nurturing an early sense of ecological responsibility. Teachers observed that children responded with greater enthusiasm when working with everyday items like bottle caps, newspapers, and cardboard. Integrating these materials into lessons not only encourages creative thinking but also introduces concepts of sustainability in a hands-on manner. Educators found this approach helpful for designing lessons that are both accessible and meaningful, inspiring children to use their imagination and care for the environment. While the findings point to recycled materials as valuable resources in early education, the study was conducted within a limited context and over a short period. Further research involving wider settings and longer observation is recommended to better understand the long-term effects. The insights gained here are relevant for educators seeking to incorporate sustainable practices and environmental values into early learning.